Synthesis of 3',5'-Cyclic Phosphate and Thiophosphate Esters of 2'-C-Methyl Ribonucleosides - Leisvuori A; Ahmed Z; Ora M; Beigelman L; Blatt L; Lonnberg H (WILEY-V C H VERLAG GMBH, 2022)
2'-C-Methylnucleosides are known to exhibit antiviral activity against Hepatitis C virus. Since the inhibitory activity depends on their intracellular conversion to 5'-triphosphates, dosing as appropriately protected 5'-phosphates or 5'-phosphorothioates appears attractive. For this purpose, four potential pro-drugs of 2'-C-methylguanosine, i.e., 3',5'-cyclic phosphorothioate of 2'-C-methylguanosine and 2'-C,O6-dimethylguanosine, 1 and 2, respectively, the S-[(pivaloyloxy)methyl] ester of 2'-C,O6-dimethylguanosine 3',5'-cyclic phosphorothioate and the O-methyl ester of 2'-C,O6-dimethylguanosine 3',5'-cyclic phosphate, 3 and 4, respectively, have been prepared.